Nonsmoking and Nondrinking Oral Squamous Cell Carcinoma Patients: A Different Entity - Yang, Zhan; Du, Wei; Zhang, Xu; Chen, Defeng; Fang, Qigen; He, Yuezhong; Yang, Yang; Li, Ding; Fan, Jie (Frontiers in Oncology, 2021)
Objective: Our goal was to analyze the demographic and pathologic characteristics as well as prognosis in nonsmoking and nondrinking (NSND) oral squamous cell carcinoma (SCC) patients compared with typical oral SCC patients. Patients and methods: A total of 353 patients were retrospectively enrolled and divided into two groups: the NSND group and the current smoking/current drinking (CSCD) group. Demographic, pathologic, and molecular data were compared between the two groups. The main research endpoints were locoregional control (LRC) and disease-specific survival (DSS). Results: In the NSND group, 16.3%, 41.9%, and 53.5% of patients were aged no more than 40 years, were female, and had an educational background of high school or above compared to 3.7%, 6.0%, and 38.2% of patients in the CSCD group, respectively. A total of 15.1% of the NSND patients had SCC of the lower gingiva and floor of the mouth, which was lower than the 35.6% of patients in the CSCD group. CSCD patients were likely to have an advanced disease stage (48.7% vs 32.5%, p=0.042) and poorly differentiated cancer (26.6% vs 16.3%, p=0.042). The NSND patients had a mean Ki-67 index of 24.5%, which was lower than the mean of 35.7% in the CSCD patients. The two groups had no HPV infection and similar p16 expression (4.7% vs 10.1%, p=0.132), but there was higher expression of p53 (38.6% vs 17.4%, p<0.001) and p63 (59.9% vs 29.1%, p<0.001) in the CSCD group. The 5-year LRC rates for NSND patients and CSCD patients were 48% and 38%, respectively, and the difference was significant (p=0.048). The 5-year DSS rates for NSND patients and CSCD patients were 56% and 39%, respectively, and the difference was significant (p=0.047). Further, a Cox model confirmed the independence of smoking and drinking status for affecting LRC and DSS. Conclusion: NSND oral SCC patients are a different entity. HPV infection has a limited role in carcinogenesis in NSND patients, and p16 expression is associated with worse locoregional control.